2007
DOI: 10.1016/j.cmet.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Coactivator PGC-1β Drives the Formation of Oxidative Type IIX Fibers in Skeletal Muscle

Abstract: Skeletal muscle must perform different kinds of work, and distinct fiber types have evolved to accommodate these. Previous work had shown that the transcriptional coactivator PGC-1alpha drives the formation of type I and IIA muscle fibers, which are "slow-twitch" and highly oxidative. We show here that transgenic expression of PGC-1beta, a coactivator functionally similar to but distinct from PGC-1alpha, causes a marked induction of IIX fibers, which are oxidative but have "fast-twitch" biophysical properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
305
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(325 citation statements)
references
References 40 publications
16
305
1
3
Order By: Relevance
“…Previous reports and our in vitro experiments ( Figure 1) demonstrated that there is mutual relationship between exercise capacity in treadmill experiments and muscular mitochondrial function 6, 9, 10, 19. We therefore further evaluated the mitochondrial status in skeletal muscle of CKD mice.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous reports and our in vitro experiments ( Figure 1) demonstrated that there is mutual relationship between exercise capacity in treadmill experiments and muscular mitochondrial function 6, 9, 10, 19. We therefore further evaluated the mitochondrial status in skeletal muscle of CKD mice.…”
Section: Resultsmentioning
confidence: 86%
“…The amount of mitochondria is regulated by both mitochondria biosynthesis and its degradation 9, 10. Tamaki et al recently reported that the amount of muscular mitochondria was decreased in the early stage of CKD mice and that it was associated with increased oxidative stress and inflammatory cytokines, such as tumor necrosis factor (TNF)‐α and interleukin (IL)‐6 6.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial biogenesis and respiration are highly dependent on the transcriptional coactivators, PGC-1α and β, and their interacting factors (Puigserver et al 1998;Wu et al 1999;Lehman et al 2000;Lin et al 2002;Kelly and Scarpulla 2004;Arany et al 2007;Sonoda et al 2007). In addition, many physiologic, hormonal and dietary cues are transduced into adaptive protein changes via the transcriptional coactivator PGC-1α.…”
Section: Pgc-1αmentioning
confidence: 99%
“…Slow fiber type genes were also shown to be upregulated by the extracellular signal-regulated kinases (ERK) pathway in rats (Murgia, et al, 2000) and by peroxisome-proliferator-activated receptor-gamma co-activator-1 alpha (PGC-1α) in mice (Lin, et al, 2002). PGC-1β, on the other hand, is involved in fast twitch (type 2X) fiber transition (Arany, et al, 2007). In human skeletal muscle in vivo there seems to be a correlation between the expression of the peroxisome proliferator-activated receptors (PPAR) α and δ and proportion of type 1 fibers (Kramer, et al, 2006, Russell, et al, 2003.…”
Section: Strategies To Improve the Human Myotube Modelmentioning
confidence: 99%